Coupling of stemness maintenance with cell cycle control in stem cells - Huang, Xia; Wang, Yujie; Li, Qiushuang; Li, Xinyi; Wang, Congcong (Frontiers in Cell and Developmental Biology, 2025)
Stem cells are undifferentiated cells characterized by their self-renewal capacity and pluripotency. The multipotent differentiation potential of stem cells grants them significant promise in clinical therapies for tissue injury and organ regeneration. Therefore, the molecular mechanisms underlying the maintenance of stem cell self-renewal and pluripotency have been a major focus of research in the field. In recent years, increasing evidence suggests that cell cycle is not only a central driver of cell division but also participate in controlling stem cell self-renewal and differentiation fate through various pathways. Stem cells, especially embryonic stem cells (ESCs), exhibit unique cell cycle features, with a notably short overall cycle duration, a significantly shortened G1 phase, and a prolonged S phase. This rapid cell cycle not only results in increased cell numbers but is also closely associated with the maintenance of their self-renewal capacity. Pluripotency states (such as naïve, formative, and primed) are tightly linked to specific cell cycle patterns, and this association exhibits species specificity. Elucidating the molecular mechanisms coupling the cell cycle with stemness maintenance is of great significance for the clinical application of stem cells. This review focuses on the cell cycle regulatory network centered around Cyclins and their inhibitors in stem cells, as well as the molecular mechanisms by which core pluripotency factors and cell cycle proteins influence stem cell fate determination. We discuss signaling pathways such as Jak1/Stat3, PI3K/Akt, and Hippo/YAP, and the role of epigenetic regulation, particularly histone modifications, in modulating the expression of differentiation-related and cell cycle-associated genes. Additionally, a brief overview is provided of the unique glycolytic metabolic mode and one-carbon metabolism in stem cells, along with their relationship with epigenetic modifications and rapid proliferative characteristics. Moreover, we analyze the regulatory functions of cell cycle regulators such as Cyclins and checkpoint protein p53 in somatic cell reprogramming and the fate determination of adult stem cells including neural and hematopoietic stem cells (HSCs). Practical strategies based on cell cycle regulation are discussed, along with prospects and challenges for their applications in regenerative medicine.